Population and Resources Linkages in Nepal - Poudel, Krishna (Himalayan Review, 2009)
Population change between 1981, 1991 and 2001 in different ecological belts, development region and the districts as well as the resources use patterns have been considered in the study. The analysis found the population number is increasing in all ecological belts however the rate is higher in the Tarai in comparison with the Hill and the Mountain. The changes in population number and demographic characteristics have been exerting considerable impact on resources utilization pattern and ultimately on environmental condition. The study has attempted to establish a linkage between population characteristics and the resources utilization and suggest the need to enhance economic opportunities, well distribution of infrastructure development, maintain production capabilities and stabilize the movement of the population for the sustainable development of the country on the whole. Key words: Population, resources, linkages, environmental degradation, regional perspectives, sustainability The Himalayan Review Vol. XXXVII, 2006 Page: 53-69